Bilateral Wrisberg discoid menisci mimicking bucket handle tears associated with osteochondritis dissecans. Issue 1 (January 2015) - Sebaaly, Amer; Boueri, Wissam; Nabhane, Linda
<x xml:space="preserve">Abstract</x> Discoid menisci are frequently associated with osteochondritis dissecans (OCD) of the knee and are often bilateral. Patients usually present with no or few symptoms disproportionate to the size of the lesions. We report the case of a 14-year-old boy who had bilateral unstable lateral discoid menisci with unilateral stage 3 OCD treated with meniscoplasty, meniscal rim stabilization, and fixation of the OCD.